2007
DOI: 10.1213/01.ane.0000278127.68312.dc
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Properties of the Ketone Bodies β-Hydroxybutyric Acid and Acetone

Abstract: Beta hydroxybutyric acid and acetone are anesthetics. Both ketone bodies enhance inhibitory glycine receptors at concentrations observed clinically in ketoacidosis. In addition, beta-hydroxybutyric acid enhances GABA(A) receptor function at these concentrations. Subanesthetic concentrations of these drugs may contribute to the lethargy and impairment of consciousness seen in ketoacidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 19 publications
2
36
1
2
Order By: Relevance
“…Nevertheless, research investigating the utilization of ketones is limited in AD; one study indicated a modest increase in SCOT expression (catabolizes ketone bodies into Acetyl-CoA and generates ATP), while the expression of HADHA and SCHAD (enzymes involved in fatty acid oxidation and ketogenesis) was significantly increased 3x in TgAD brain [46]. Although many studies reported the neuroprotective effect of ketogenic diets [47], the continued accumulation of 3-hydroxybutyric acid from non-dietary sources could diminish the interfacial viscosity of membrane lipids and modulate ion channels and thus disturb higher brain function [48, 49]. Furthermore, our findings shown that cognitive impairment was associated with serine level aberrations after chronic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, research investigating the utilization of ketones is limited in AD; one study indicated a modest increase in SCOT expression (catabolizes ketone bodies into Acetyl-CoA and generates ATP), while the expression of HADHA and SCHAD (enzymes involved in fatty acid oxidation and ketogenesis) was significantly increased 3x in TgAD brain [46]. Although many studies reported the neuroprotective effect of ketogenic diets [47], the continued accumulation of 3-hydroxybutyric acid from non-dietary sources could diminish the interfacial viscosity of membrane lipids and modulate ion channels and thus disturb higher brain function [48, 49]. Furthermore, our findings shown that cognitive impairment was associated with serine level aberrations after chronic stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, as KB had historically been viewed as metabolic substrates and not direct modulators of synaptic function, it was therefore not surprising that investigators found that clinically relevant (i.e., low millimolar) concentrations of BHB and ACA did not affect GABA A receptors, ionotropic glutamate receptors, or voltage-gated sodium channels in normal rodent hippocampus [30, 31]. From this point, the hunt for novel potential mechanisms commenced and to date has yielded a few very intriguing candidates.…”
Section: Molecular Targets Of Ketone Body Actionmentioning
confidence: 99%
“…Whole cell currents were studied with a -80 mV holding potential using standard 2-electrode voltage clamping techniques. Methods for measuring whole-cell GABA A receptor currents have been described [5,[11][12][13] . Briefly, pairs of identical concentrations of the phenyl compound were prepared in glass syringes containing frog ringer's (FR) solution (115 mmol/l NaCl, 2.5 mmol/l KCl, 1.8 mmol/l CaCl 2 , and 10 mmol/l HEPES in 18.2 MΩ H 2 O, filtered and adjusted to pH 7.4) or FR + agonist (FR-GABA; FR plus 20-40 μmol/l, GABA, equal to an EC [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%